From Service to Success: Management Strategies in Facilitating SME Growth within Communities - Rosadi, Nina (Golden Ratio of Community Services and Dedication, 2024)
This research investigates management strategies facilitating Small and Medium-sized Enterprises (SMEs) growth within communities. The study aims to explore key factors and mechanisms enabling SMEs to overcome challenges and achieve sustainable growth. Adopting a quantitative descriptive approach, data was collected through surveys, interviews, and statistical analysis. Thematic analysis revealed several crucial insights. Firstly, innovation adoption, particularly open innovation, emerged as a critical strategy for SME competitiveness and success. Secondly, strategic partnerships play a pivotal role in accessing resources and markets, enhancing SMEs' international presence. Thirdly, human resource management practices, including talent management and digital HR, are essential for enhancing organizational performance and adaptability. Moreover, the COVID-19 pandemic accelerated digitalization among SMEs, emphasizing the importance of resilience planning. Additionally, community engagement remains fundamental, enabling SMEs to build trust, legitimacy, and social capital. The research contributes to understanding the complex dynamics of SME growth within communities, offering actionable insights for policymakers, business owners, and community stakeholders.